2021
DOI: 10.15578/squalen.536
|View full text |Cite
|
Sign up to set email alerts
|

Antipathogenic Activity of Acroporid Bacterial Symbionts Against Brown Band Disease-Associated Bacteria

Abstract: The coral reefs’ condition in most regions in Indonesia has been declining due to coral diseases, such as Brown Band Disease (BrBD). A treatment for BrBD involves the use of biological control agents that have antagonistic properties against disease-causing agents. This study aimed to isolate bacteria from healthy hard coral, those associated with BrBD, and those that had bioactivities against BrBD. Sampling and identification of corals and BrBD were carried out in March 2015 at the Marine National Park of Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The antagonistic activity of coral-associative bacteria was tested using the double-layer method [15]. Healthy coral bacterial isolates were dotted on the surface of Zobell 2216E agar medium and incubated for 96h at 27°C.…”
Section: Antagonistic Assaymentioning
confidence: 99%
“…The antagonistic activity of coral-associative bacteria was tested using the double-layer method [15]. Healthy coral bacterial isolates were dotted on the surface of Zobell 2216E agar medium and incubated for 96h at 27°C.…”
Section: Antagonistic Assaymentioning
confidence: 99%
“…PCR reaction with a total of 25μL consisted of 2.5 μL DNA template, each primer of 2.0 μL, ddH2O of 6 μL, and mix PCR (MyTaqTMRed Mix-Bioline) of 12.5 μL. The amplification reaction was carried out in a Thermal Cycler (BIO-RAD) T100 in accordance with Amalia et al (2021), the specific steps are as follows: Initial denaturation at 95°C for 3 minutes; 30 cycles of denaturation at 95°C for 1 minute, then annealing at 55°C for 1 minute, extension at 72°C for 1 minute, and final extension at 72°C for 7 minutes. The PCR products were examined using gel electrophoresis with agarose 1%, and the result was visualized by using UVIDoc HD5 (UVITEC Cambridge, UK).…”
Section: Dna Extraction and Amplification Of 16s Rrna Genementioning
confidence: 99%
“…Molecular identification was conducted for the most active sponge-associated bacteria (Table 1) by comparing 16S rRNA genes of the isolates with similar bacteria (Amalia et al 2021). As demonstrated in Figure 2, all isolates have amplicons with a size of approximately 1,500 bp (Amalia et al 2021), indicated by the bands in the 1,500 bp DNA ladder region.…”
Section: Molecular Identification Of Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation